COMPARISON OF GENDER IN THE PERCEPTION OF THE IMAGE AND ITS RELATIONSHIP WITH THE BRAND POSITIONING - de la Vega, Laura Estela Fischer; Arévalo, Oscar Zamora; Sánchez, David Chávez (European Scientific Journal, ESJ, 2013)
The brand exposure in graphic communication, require seconds to transmit the message that persuade the consumer to make the purchase, hence finding appropriate images is an important aspect for marketing managers. The images themselves convey emotion and the perception of them may be altered by the brand positioning. The way images are perceived may differ by gender; and also, the perception that people have of a brand can impact differently on each of them. In this experimental study, the main objective is to examine the relationship between the effects of brand image exposure to affective visual stimuli, differentiated by gender. 274 students (19 years old) from the Management School of the National University of Mexico participated in this study. 60 photos from the IAPS (International Affective Picture System) representing different emotional loads were used, each of them was embedded with a well-recognized and positioned brand in the market taken from the list of BrandZ, and Millward Brown top 100 (2010). The images were evaluated by a Likert scale with nine intervals. The results obtained suggest that the effect of the picture is different in each gender and this effect is modified by the impact of brand positioning on men and women differently. The results will have specific knowledge about the differential impressions of an image and the perception of the brand, so that marketing managers may have a greater impact on attention and memory in the design of their graphic campaigns.